2020
DOI: 10.3846/jcem.2020.12316
|View full text |Cite
|
Sign up to set email alerts
|

An Association Rule Mining Model for the Assessment of the Correlations Between the Attributes of Severe Accidents

Abstract: Identifying the correlations between the attributes of severe accidents could be vital to preventing them. If such relationships were known dynamically, it would be possible to take preventative actions against accidents. The paper aims to develop an analytical model that is adaptable for each type of data to create preventative measures that will be suitable for any computational systems. The present model collectively shows the relationships between the attributes in a coherent manner to avoid severe acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 69 publications
(94 reference statements)
1
12
0
Order By: Relevance
“…-In Tree Level 2 and Rule Number IV, 30% of workers who were struck by falling objects, bitten/stung/scratched, and caught in or between objects had serious/ fatal injuries because PPE was not provided. In a similar study, "being struck by an object" was the most observed and fatal accident type that generally occurred during operations (Ayhan et. al., 2020).…”
Section: Resultsmentioning
confidence: 91%
“…-In Tree Level 2 and Rule Number IV, 30% of workers who were struck by falling objects, bitten/stung/scratched, and caught in or between objects had serious/ fatal injuries because PPE was not provided. In a similar study, "being struck by an object" was the most observed and fatal accident type that generally occurred during operations (Ayhan et. al., 2020).…”
Section: Resultsmentioning
confidence: 91%
“…The association rule method (ARM) is very popular in accident analysis. Ayhan et al (2020) used ARM to identify the attributes of severe accidents and concluded that the most common attribute in various accidents is that personnel cannot perceive external risks. Yang (2020) constructed a logistics financial risk ontology model based on ontology and association rules.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2019). In the European Union (EU), as well as the USA, construction accounts for a full one-fifth of accidents reported across all industries (Ayhan et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The myriad uncertainties and risks involved in such endeavors, combined with an intense labor dependence (Ayhan and Tokdemir, 2019), results in relatively high rates of occupational injuries (Bavafa et al, 2018;Jin et al, 2019). In the European Union (EU), as well as the USA, construction accounts for a full one-fifth of accidents reported across all industries (Ayhan et al, 2020). Moreover, over the period 2010 to 2016, the number of occupational health and safety (OHS)-related injuries increased 28%, with some 991 fatalities in 2016 (Al-Bayati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%